An infinite-dimensional Borsuk-Ulam-type generalization of the Leray-Schauder fixed-point theorem and some applications - Prykarpatsky, A.K. (Український математичний журнал, 2008)
A generalization of the classical Leray – Schauder fixed point theorem, based on the infinite-dimensional Borsuk – Ulam type antipode construction, is proposed. A new nonstandard proof of the classical Leray – Schauder fixed point theorem and a study of the solution manifold to a nonlinear Hamilton – Jacobi type equation are presented. Запропоновано узагальнення класичної теореми Лерея - Шаудера про нерухому точку, що ґрунтується на нєскінчєнновимірній конструкції антиподiв типу Борсука-Улама. Наведено нестандартне доведення класичної теореми Лерея - Шаудера про нерухому точку та досліджено многовид розв'язків нелінійного рівняння типу Гамільтона-Якобі.